The labour markets in Finland, Germany, Latvia, Norway, and Sweden 2006-2010 - Sabine Klinger; Eugen Spitznagel; Johanna Alatalo; Karin Berglind; Håkan Gustavsson; Hans Kure; Ilkka Nio; Janis Salmins; Vita Skuja; Johannes Sorbo (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2012)
Via the International Labour Market Forecasting Network, forecasters of the public employment services or comparable institutes from the Nordic countries as well as Germany and Austria exchange their analyses about the current and future development of the national economies and labour markets. This report documents some of the discussions during the past few years. Finland, Germany, Latvia, Norway, and Sweden exemplify their starting conditions and labour market reactions to the Great recession in 2008 and 2009. – – Im International Labour Market Forecasting Network tauschen sich Prognostiker der öffentlichen Arbeitsverwaltungen und verwandter Institute aus den nordischen Ländern sowie Deutschland und Österreich regelmäßig über die aktuelle und erwartete Entwicklung der nationalen Volkswirtschaften und Arbeitsmärkte aus. Dieser Bericht dokumentiert in Kürze die Diskussion in den zurückliegenden Jahren. Beispielhaft skizzieren Finnland, Deutschland, Lettland, Norwegen und Schweden den Ausgangspunkt und die Reaktionen ihrer Arbeitsmärkte auf die Große Rezession 2008/09.
Keywords: 330; Arbeitsmarktentwicklung - internationaler Vergleich; Wirtschaftskrise - Dauer; Finanzkrise - Auswirkungen; Beschäftigungseffekte; Arbeitslosigkeit; Arbeitsmarktprognose; Rezession; Zukunftsperspektive; Arbeitsproduktivität; Finnland; Norwegen; Lettland; Schweden; Bundesrepublik Deutschland; Arbeitsmarkt; Wirtschaftskrise; Arbeitslosigkeit; Finnland; Deutschland; Lettland; Norwegen; Schweden